African developments: continental integration in Africa - AU, NEPAD and the APRM - Sven Grimm; George Katito (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Africa has seen political and institutional change over the last decade, yet in the 50th year of independence of numerous states, the profundity of change remains unclear. The prospect of successful continental integration has arguably suffered a loss of political drive with the absence of authoritative, clear minded political leadership - two of the key champions of the `African renaissance', Olusegun Obasajano of Nigeria and Thabo Mbeki of South Africa, have both exited office. There is a dearth of energetic leadership with the drive to promote integration – and arguably an even greater dearth of strong and viable institutions on the continent. New institutions have been created: in 2001, the New Partnership for Africa's Development (NEPAD) was established, the Organisation of African Unity (OAU) was transformed into the African Union (AU) in 2002 and the African Peer Review Mechanism (APRM) was created. However, while these institutions share an intertwined history, interaction between them is often poor. Organisational mandates overlap while the conflicting interests of African states stifle delivery on Africa's governance and development agenda. Despite similarity in names, the AU is not comparable with the EU. External partners should thus avoid overly ambitious expectations towards a fundamentally still intergovernmental international organisation. Regional organisations will have to be considered when looking for partners in Africa. External partners should, however, measure the AU on its declarations and engage with it, as it is the best bet on integration there currently is.
Keywords: 330